Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. - Azevedo, F.; Padua, A.; Moraes, F.; Rossi, A.; Muricy, G.; Klautau, M. (Zootaxa, 2017)
Despite the enormous economic, scientific and strategic value of the Brazilian oceanic and mid-shelf islands (BOMIs), the biological communities of these islands are still poorly known. An example is their fauna of calcareous sponges (Porifera: Calcarea), with only six species described up to date. In the present study, we analysed the Calcinean sponges from the mid-shelf Abrolhos Archipelago and four of the five Brazilian oceanic islands (São Pedro e São Paulo Archipelago, Fernando de Noronha Archipelago, Rocas Atoll, and Trindade Island), using both morphological and molecular approaches for taxonomy. Fourteen species were found, of which 12 are new to science: Arturia trindadensis sp. nov., Borojevia tenuispinata sp. nov., B. trispinata sp. nov., Clathrina insularis sp. nov., C. lutea sp. nov., C. mutabilis sp. nov., C. zelinhae sp. nov., Ernstia citrea sp. nov., E. multispiculata sp. nov., E. rocasensis sp. nov., E. sanctipauli sp. nov., and E. solaris sp. nov. These results raised in 63% the species richness of calcareous sponges from the BOMIs. Clathrina aurea and Leucetta floridana were recollected and the former had its geographical distribution expanded. The molecular tree obtained confirmed the morphological identifications and allowed a discussion about the evolution of morphological characters, and the usefulness of some of those characters in the taxonomy of Calcinea.